Effect of Antiepileptics on Retinal Blood Flow in Adults Wister Rats - Shumaila Shakoor, Uruj Zehra, Sabahat Zulfiqar, Muhammad Bahadur Baloch, Rahat Bano Siddiqui, M. Muneeb Athar, Shamaila Ejaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Effect of Antiepileptics on Retinal Blood Flow in Adults Wister Rats SHUMAILA SHAKOOR1, URUJ ZEHRA2, SABAHAT ZULFIQAR3, MUHAMMAD BAHADUR BALOCH4, RAHAT BANO SIDDIQUI5 MUHAMMAD MUNEEB ATHAR6, SHAMAILA EJAZ7 1Assistant Professor of Anatomy, Lahore Medical & Dental College, Lahore 2Head of Anatomy Department, UHS, Lahore 3Assistant Professor of Anatomy, Nawaz Sharif Medical College, Gujrat 4Assistant Professor Anatomy, FMH College of Medicine & Dentistry, Lahore 5Assistant Professor of Anatomy, Fazaia Ruthpfau Medical College, Karachi 6Senior demonstrator Anatomy, Sahiwal Medical College, Sahiwal 7Senior Demonstrator Anatomy, Lahore Medical & Dental College, Lahore Correspondence to Dr. Shumaila Shakoor, Email: shumailashakoor303@gmail.com, Cell: 0335-0888446 ABSTRACT Background: Carbamazepine (CBZ) is an effective antiepileptic drug (AED) used as first line of drug for of partial and convulsive generalized epilepsy in all age groups. Most common clinically reported side effect of CBZ is blurry or double vision. How it affects retinal histological architecture has not been explored yet. Aim: To observe the light microscopic retinal changes in adult Wistar albino rats after administration of CBZ. Methods: The experiment was conducted in University of Health Sciences, Lahore after the approval of ethical review committee. 18 Rats were randomly divided into 3 groups of 6 rats each. Group A served as control and was given 1ml saline alkalinized with 0.1N NaOH, Group B&C were given CBZ 50 mg/kg and 100 mg/kg respectively dissolved in 1ml saline alkalinized with 0.1N NaOH in 3 divided doses intraperitoneally for 7 days. Animals were sacrificed on 8th day, and retinal tissue sections of 5µm were stained for H& E to look for vascular congestion in retinal layers (yes/no). Chi2 was applied for statistical analysis using SPSS v 20. Practical implications: ophthalmic examination mandatory for epileptic patients on long term use of AED. Results: vascular congestion was seen among layers of retina in dose dependent manner in experimental groups (p=0.006) Conclusion: The findings of the present study indicates that CBZ affects retina blood flow, can impose a potential risk to visual disturbances. Key words: vascular congestion, epilepsy, carbamazepine (CBZ)